New insights of the tectonic and sedimentary evolution of the Rio Grande Rise, South Atlantic Ocean - Pinheiro Praxedes, Adriane Gomes; de Castro, David Lopes; Torres, Luiz Carlos; Gambôa, Luiz Antônio Pierantoni; Hackspacher, Peter Christian [UNESP] (Elsevier, 2019)
Oceanic plateaus, such as the Rio Grande Rise (RGR), comprise crucial pieces of information about the opening of the South Atlantic Ocean and the evolution of associated lithospheric plate margins. A detailed seismostratigraphic assessment of the volcano-sedimentary package of the RGR was conducted in its western portion based on correlations between seismic data and DSDP Site 516F. The approximately 330-km long seismic transect is characterized by a complex array of normal faults related to extensional tectonics from Late Cretaceous to the Miocene, and probably into the present-day, along the Cruzeiro do Sul Rift. The bathymetric and seismic data reveal: a) the presence of deep faults that rise from the basement to the sea floor; b) the occurrence of several seamounts with tops at a water depth below 1000 m; and c) prominent graben structures that represent unidentified volcanic intrusions, indicative of the reactivation of Lower Miocene faults by younger extensional events. Based on integration of older data with the results presented here, we propose a five-stage tectono-sedimentary model for the western portion of the RGR: 1) the first basaltic flow began to form the Rio Grande Rise in the Coniacian/Santonian; 2) extensional movements caused rifting during the uplift of the large volcanic structures; 3) volcanic islands emerged above sea level increasing the deposition of volcanic breccia and ash layers; 4) after the volcanism ceased, thermal subsidence took place over the entire rise with intense erosion and sedimentation; and 5) the uppermost sedimentary layers were deposited in pelagic conditions and offset by sub-vertical normal faults.
Keywords: Cruzeiro do Sul Rift; Magmatism events; Rifting; Rio Grande Rise; Seismic interpretation; Tectono-sedimentary evolution